Risk management–control system interplay: case studies of two banks. Issue 4 (7th November 2016) - Rad, Alexander
Abstract : Purpose: This paper aims to explore the interplay between risk management and control systems in banks, specifically investigating the managerial intentions underlying the design of management control systems. Design/methodology/approach: This study is based on 31 interviews with personnel of two banks in a European country. Findings: The main finding is that belief systems drive the interplay between risk management and control systems in the studied banks. In several instances, belief systems and boundary systems were operating complementarily. Cross-case analyses of the two banks demonstrate that risk management (i.e. the Basel II Accord) replaced established operating procedures for loan origination and portfolio monitoring at the first bank, whereas senior managers suppressed Basel II to maintain established loan origination and portfolio monitoring procedures at the second one. Originality/value: This is one of very few studies investigating the interplay between risk management and control systems in banks.